2011
DOI: 10.1007/s00401-011-0858-3
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor (MIF) expression in human malignant gliomas contributes to immune escape and tumour progression

Abstract: Macrophage migration inhibitory factor (MIF), which inhibits apoptosis and promotes angiogenesis, is expressed in cancers suppressing immune surveillance. Its biological role in human glioblastoma is, however, only poorly understood. We examined in-vivo expression of MIF in 166 gliomas and 23 normal control brains by immunohistochemistry. MIF immunoreactivity was enhanced in neoplastic astrocytes in WHO grade II glioma and increased significantly in higher tumour grades (III-IV). MIF expression was further ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 54 publications
9
67
0
Order By: Relevance
“…For example, a previous study demonstrated that in gastric cancer, positive MIF expression rates were 12, 52 and 96% in normal mucosal, gastritis and gastric cancer tissues, respectively (18). Similar observations have also been reported in pancreatic cancer, melanoma, hepatocellular carcinoma, malignant glioma and cervical adenocarcinoma (13,(19)(20)(21)(22).…”
Section: Mif and Carcinogenesissupporting
confidence: 72%
See 1 more Smart Citation
“…For example, a previous study demonstrated that in gastric cancer, positive MIF expression rates were 12, 52 and 96% in normal mucosal, gastritis and gastric cancer tissues, respectively (18). Similar observations have also been reported in pancreatic cancer, melanoma, hepatocellular carcinoma, malignant glioma and cervical adenocarcinoma (13,(19)(20)(21)(22).…”
Section: Mif and Carcinogenesissupporting
confidence: 72%
“…MIF-silencing studies have revealed comparable reductions in the tumor cell proliferation of human melanoma and hepatocellular carcinoma cell lines, whereby a decrease in cyclin D1 expression was reported in vitro and in vivo, respectively (31,20). Another study reported that cyclin-dependent kinase 4, cyclin D2 and cyclin E2 expression was downregulated following MIF-knockdown in HeLa 229 cells (22). In hepatocellular carcinoma, increased MIF expression, induced by cell transfection, potentiated the promoter activity of the hepatopoietin gene (a mediator involved in liver regeneration), leading to enhanced cell proliferation (40).…”
Section: Mif and Cell Proliferation Shi Et Almentioning
confidence: 93%
“…Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression. However, our data suggest that CD74 expression alone is not an independent marker for poor prognosis and it requires the expression of MIF for tumor pathogenesis, as previously reported in other studies (4,7,16,17,18) . Although we did not perform co-localization staining for MIF-CD74 in this retrospective study, evidence of MIF and CD74 co-localization reported in several other studies (7,8,9,10,11,12,13,14) .…”
Section: Discussionsupporting
confidence: 77%
“…In line with this observation, we demonstrated overexpression of MIF in grade II-IV astrocytoma, and that overexpression of CD74 is associated with tumor progression in astrocytoma at the gene and transcription levels. MIF exerts multimodal functions in glioblastoma including pro-proliferative, promigratory, pro-angiogenic as well as immune-evasive properties through CD74 (16,17,18) . The binding of MIF to the extracellular domain of CD74 is necessary as an initial step in the MIF signaling cascade (4) resulting in tumor vascularization and the promotion of neoplastic Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Even more importantly, MIF seems to be required for bone marrow-derived dendritic cells to maintain mature B cells in the bone marrow compartment. 23 MIF is overexpressed in a variety of malignancies compared with the respective primary tissues (eg, prostate, 24 colon, 25 melanoma, 26 glioblastoma, 27 breast cancer 28,29 ). This overexpression might be caused by the tumor-activated HSP90 chaperone complex that protects MIF from degradation, as shown in an ErbB2 transgenic mouse model of human HER2-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%